Expectant management for umbilical artery thrombosis in the third trimester of pregnancy: a case report - Gong, Mei-Qin; Zhang, Yong-Qing; Wang, Xiao-Dong (Frontiers in Pharmacology, 2024)
Background: Umbilical artery thrombosis (UAT) is a rare complication of pregnancy and is associated with adverse pregnancy outcomes, including fetal intrauterine distress, intrauterine growth restriction, and still birth. UAT is unpredictable, and prenatal diagnosis is challenging. There is no consensus on the treatment strategy of UAT, especially for patients with prenatal detection of one of the umbilical artery embolisms. In most previous cases, an emergency cesarean section was performed, or intrauterine fetal death occurred at the time of UAT diagnosis. Case presentation: In this report, we describe a case of thrombosis in one of the umbilical arteries detected by routine ultrasonography at 31+3 weeks of gestation in a 34-year-old woman. Following expectant management with intensive monitoring for four days, an emergency cesarean section was performed because of abnormal fetal umbilical cord blood flow and middle cerebral artery blood flow; the newborn was in good condition at birth. The final umbilical cord histopathology revealed thrombosis in one of the umbilical arteries. Both mother and newborn described in this case underwent long-term follow-up for nearly two years and are currently in good health without any complications. Conclusions: Based on our experience, obstetricians should comprehensively consider the current gestational age and fetal intrauterine status when UAT is suspected to determine the best delivery time. The appropriate gestational age should be prolonged as long as the mother and fetus are stable when the fetus is immature, trying our best to complete the corticosteroid treatment to promote fetal lung maturity and magnesium sulfate to protect fetal brain. During expectant management, ultrasound monitoring, electronic fetal heart monitoring, and fetal movement counting should be strengthened. Clinicians should ensure that the patients and their families are informed about all potential risks of expectant management for UAT.